Effects of dietary compound acidifier (Biomin) on the growth, anti-oxidation, immunity, and intestinal health of juvenile channel catfish (Ictalurus punctatus) - Junyu Yan; Kai Luo; Bo Wang; Jiaxin He; Can Li; Jiang Zhou; Wenhao Lai; Xin Zhou; Jingwei Ye; Mingzhu Pan; Yingbing Su; Weihua Gao; et al. (Aquaculture Reports)
The current study was conducted to investigate the influences of dietary compound acidifier (CA, Formic acid (45 %), malic acid (0.3 %), Fumaric acid (0.6 %) and Succinic acid (0.6 %), Biomin Feed Additives (Shanghai) Ltd) on the growth, anti-oxidation, immunity, and intestinal health of channel catfish (Ictalurus punctatus). Six experimental diets (about 36 % crude protein and 5 % crude lipid) were prepared with graded levels of dietary CA (0 (control), 0.05 %, 0.10 %, 0.20 %, 0.40 %, and 0.80 %). A total of 648 fish with similar initial body weight (143.77 ± 0.73 g) were randomly placed into 18 tanks, with 36 fish in each tank. Fish were hand-fed to apparent satiation thrice daily for 72 days (water temperature was 25–27℃). The results showed that the WGR (weight giant rate) and SGR (specific growth rate) of channel catfish in the 0.10 % group were significantly increased compared with the control group (P < 0.05). The broken line model revealed that 0.0863 % of dietary CA was recommended for optimal SGR. The SOD (superoxide dismutase) activity and MDA (malondialdehyde) content in the serum in the 0.10 % groups were remarkably increased and decreased compared with the control group, respectively (P < 0.05). The ACP (acid phosphatase), LZM (lysozyme) activities and ALB (albumin) contents in the serum were significantly increased after supplementation of 0.10–0.40 %, 0.10–0.20 % and 0.40–0.80 % of dietary CA, respectively (P < 0.05). The AKP (alkaline phosphatase) activity in the serum in the 0.05 % and 0.10 % groups was decreased compared with other groups (P < 0.05). The GOT (glutamic oxalacetic transaminase) and GPT (glutamic pyruvic transaminase) activities in the serum notably decreased by 0.10–0.20 % and 0.05 % of dietary CA, respectively (P < 0.05). The T-CHO (total cholesterol) and HDL-C (high density lipoprotein cholesterol) contents in the serum increased by 0.80 % and 0.05 %-0.80 % of dietary CA (P < 0.05). The TG (triglyceride) content in the serum was lowest in the 0.10 % group. The expression levels of gh (growth hormone), ghr (growth hormone receptor), igf-1 (insulin-like growth factors 1), igf-2, igfbp-1 (insulin-like growth factor-binding proteins-1), igfbp-2 and igfbp-3 in the liver of the 0.10 % group were significantly higher than the control and 0.08 % groups (P < 0.05). The level of tgf-β (transforming growth factor beta), il-10 (interleukin 10), caspase3, caspase7, caspase9, occludin, zo-1 (zonula occludens-1), zo-2, claudin-12, claudin-15a, claudin-15b in the intestine of the 0.10 % group significantly increased compared with the control group (P < 0.05). Supplementation of 0.10 % dietary CA could improve the microbial diversity in the intestine of channel catfish. In conclusion, adding 0.10 % of dietary CA to the diet could improve the growth performance, anti-oxidative capacity, immunity, and intestinal health of channel catfish. Based on the SGR, the recommended optimal level of CA for channel catfish was 0.0863 %. The mechanisms regulating the growth-promoting and health-improving effects of CA on channel catfish need to be further investigated.